Efecto del abono orgánico en el cultivo de tomate lycopersicum esculentum variedad heatwave vffnt - Gaona Medina, Darwin Euclides (2006)
The present work was carried out in Mr. Alonso Campoverde's property Campoverde"de property, located in the parish The Change, belonging to the Cantón Machala, of the county of the Gold, to 4.5 Km. of the city of Machala, with geographical location corresponding to Latitude: 03º 17´16´´ south, Longitude: 79º 57´05´´ west and Altitude: 6 m.s.n.m, The area is considered an ecological formation that corresponds to the tropical very dry forest (bms-T) according to Holdridge, with a temperature I average yearly of 24.9ºC, and a precipitation of 500 mm I average yearly, the Answer of the tomato Heatwave VFNNT was studied (Lycopersicum esculentum.). to the application of organic payments. The objectives were: 1. to determine the effectiveness of the organic payments in the tomato cultivation, 2. to Select the organic payment and dose adapted in the tomato production, 3. to Carry out the economic analysis. the used treatments were the following ones: T1:Biol with 18.24 Lt, T:2 worm Humus with 30.4 Kg, T3: Bokashi with 30.4 Kg T4 Vitagres with 6.1 Lt and the witness that any treatment was not applied. The products were applied in parcels fixed totally at random in a design in blocks in factorial arrangement with 6 treatments and 4 repetitions, totalling 24 experimental units. During the development of the cultivation she/he was given the cultural works: I water and controls fitosanitarios. The treatments were applied by means of incorporations to the floor and by means of aspersions foliares to the controls fitosanitario that were applied with a bomb CP3 previous calibration of the aspersion volume and the corresponding dose. The following variables were evaluated:, Height of the plant at the 30, 60 days, Days to the floración, Days to the fructificación, I Number of fruits for plant, Diameter of a fruit Weight of a fruit in Kg, Yield kg/ha and Incidence of Plagues and illnesses., With the organic payments you achieves potenciar the productive capacity of the one tomato, the best treatments were those of Bokashi and Biol in comparison with the other treatments.